Investigation of infant deaths associated with critical congenital heart diseases; 2018–2021, Türkiye - Nilgün Çaylan; Sıddika Songül Yalçin; Başak Tezel; Oben Üner; Şirin Aydin; Fatih Kara (BMC Public Health, 2024)
Abstract Background The aim of this study was to examine the characteristics of infant mortality associated with critical congenital heart disease (CCHD). Methods In a cross-sectional study, data for the study were obtained through Death Notification System, Birth Notification System and Turkish Statistical Institute birth statistics. Results Of all infant deaths, 9.8% (4083) were associated with CCHD, and the infant mortality rate specific to CCHD was 8.8 per 10,000 live births. CCHD-related infant deaths accounted for 8.0% of all neonatal deaths, while the CCHD specific neonatal death rate was 4.6 per 10,000 live births. Of the deaths 21.7% occurred in the early neonatal, 30.3% in the late neonatal and 48.0% in the post neonatal period. Group 1 diseases accounted for 59.1% (n = 2415) of CCHD related infant deaths, 40.5% (n = 1652) were in Group 2 and 0.4% (n = 16) were in the unspecified group. Hypoplastic left heart syndrome was the most common CCHD among infant deaths (n = 1012; 24.8%). The highest CCHD related mortality rate was found in infants with preterm birth and low birth-weight while multiparity, maternal age ≥ 35 years, twin/triplet pregnancy, male gender, maternal education in secondary school and below, and cesarean delivery were also associated with higher CCHD related infant mortality rate. There was at least one non-cardiac congenital anomaly/genetic disorder in 26.1% of all cases. Conclusion CCHD holds a significant role in neonatal and infant mortality in Türkiye. To mitigate CCHD-related mortality rates, it is crucial to enhance prenatal diagnosis rates and promote widespread screening for neonatal CCHD.